Ultrasound Promoted One Pot Synthesis of 14-Aryl-14H-dibenzo[a,j]xanthene Derivatives - M.A. Al-Kadasi, Abdulkarim; Nazeruddin, G.M. (Asian Journal of Chemistry, 2011)
A simple and facile ultrasound promoted one pot synthesis of 14-aryl-14H-dibenzo[a,j]xanthene derivatives, via perchloric acid catalyzed condensation reaction of β-naphthol and aryl aldehydes is described, having the advantages of excellent yields, short reaction time and mild reaction conditions.